Skin microvascular perfusion change with arteriovenous fistula creation in chronic kidney disease - Cheng, Chai Siew (2017)
Introduction: Matured native arteriovenous fistula (AVF) is an optimal vascular access for supporting the haemodialysis blood circuit. Maturation of AVF involved complex vascular remodeling including shunting of blood flow from arterial system toward the low resistance venous limb. In this study, we would like to evaluate the change of skin microvascular perfusion over the extremity with AVF maturation by using laser doppler flowmetry. Method: Total of 45 consented patients with chronic kidney disease (CKD) Stage IV-V who underwent AVF creation over upper extremity from July 2014 to Jun 2016 at Hospital Universiti Sains Malaysia were included in this study. The measurement of skin microvascular perfusion was done with laser doppler flowmetry pre-operative and post operative day 1, week 2, week 6 and week 12. Assessment of AVF maturation was done by 6 weeks. Result: Thirty-two patients with mean age of 55.6 (20 male, 12 female) had achieved AVF maturation. There were 13 (40.6%) radial-based and 19 (59.4%) brachial-based AVF. There was 32.8% reduction of mean skin perfusion distal to the fistula by day 1 compare to baseline perfusion but perfusion increased back by 47% by Week 2 compare to day 1 and no dramatic change upon AVF maturation. At the area proximal to anastomosis AVF, there was increasement of mean skin perfusion over 12 weeks with 35.8% at day 1 from baseline. However, the change of mean skin perfusion was not statistically significant. There was also no significant relation of skin perfusion change with the type of fistula, diabetes mellitus, hypertension and hyperlipidemia. Conclusion: Laser doppler flowmetry successfully detected the subclinical change of skin microvascular perfusion relation with AVF creation and maturation. Reduction of skin perfusion distal to the fistula suggested that in patients with existing perfusion inadequacy of extremities may experiences ischemic symptom as early as day 1 post operation and need close monitoring for distal limb ischemic-related complications.